Peningkatan Inklusivitas Pendidikan Melalui Taman Belajar Oleh Mahasiswa KKN UMD 02 Desa Binakal Bondowoso - Firmansyah, Febby (Bersatu: Jurnal Pendidikan Bhinneka Tunggal Ika, 2024)
Education is important in the development of individuals and society. Through education, humans can improve the knowledge, skills and character needed to face the challenges of an increasingly complex world. The disparity between regions and the lack of access to education are obstacles to education. This gap can occur due to differences in educational facilities and quality between cities and villages. Therefore, educational inclusiveness efforts are urgently needed to ensure that all people have equal opportunities to receive education, both through formal and informal education. Universities also have a role in advancing society. Through programs such as Kerja Kuliah Nyata (KKN), students can contribute to solving problems in society. In this context, University of Jember Community Service Program 002 students carried out the UMD (Unej Membangun Desa) program by building a Learning Park in Binakal Village, Bondowoso. This village has unique geographical conditions, as well as limited access to formal education. The aim of this program is to provide non-formal learning facilities for village children to get additional education outside of school hours. Socialization is carried out in elementary schools, and intensive learning methods are applied by mentor students.